2009
DOI: 10.1177/0957926509106411
|View full text |Cite
|
Sign up to set email alerts
|

Racism and xenophobia in immigrants’ discourse: the case of Argentines in Spain

Abstract: This study examines how racist and xenophobic discourses of Spanish elite groups are appropriated and contested in an Internet forum for Argentines in Spain. Specifically, I examine the discursive strategies involved in the identification of the in-group and the out-group (Spanish citizens vs immigrants), the descriptions of the social actors, and the stances adopted by the participants in the forum, three dimensions that have been found to be key in the production of xeno-racist discourses. The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Research on immigrants has shown that they are commonly stereotyped as likely to become involved with crime (Del-Teso-Craviotto, 2009;Dingeman and Rumbaut, 2010). Stereotypes in SA include 'foreigners are crooks' and being involved in 'sophisticated crime' as captured in (32)(33)(34)(35)(36)(37).…”
Section: Topos Of Crime Threatmentioning
confidence: 99%
“…Research on immigrants has shown that they are commonly stereotyped as likely to become involved with crime (Del-Teso-Craviotto, 2009;Dingeman and Rumbaut, 2010). Stereotypes in SA include 'foreigners are crooks' and being involved in 'sophisticated crime' as captured in (32)(33)(34)(35)(36)(37).…”
Section: Topos Of Crime Threatmentioning
confidence: 99%
“…and in the discursive strategies and interactions of and between non‐elites. van Dijk’s foundational work examined racism in news media (1987, 1991; see also Teo 2000) and in politics, education, and corporations (1993b; see also Del‐Teso‐Craviotto 2009 and Martin‐Rojo and van Dijk 1997). He has also examined the ways in which elite articulations of racial attitudes are linguistically mitigated (1992, 2000; see also Bonilla‐Silva and Forman 2000) and reproduced through the text and talk of non‐elites (1987, 1993b).…”
Section: Overview Of Researchmentioning
confidence: 99%
“…Del‐Teso‐Craviotto (2009) examines the ways in which the xenophopic and racist discourse of Spanish elites filters down to Argentinian immigrants. Noting the need for research on how the subjects of racist discourse respond to elite xeno‐racist ideology, the author analyzes how participants in an Internet forum appropriate, contextualize, and, sometimes, embrace elite discourses about them (586).…”
Section: Overview Of Researchmentioning
confidence: 99%
“…Here we focused on linguistic choices, which constructed Zimbabwean women migrants as victims and transmitters of debauched behaviour. It has been reported in the literature (Del-Teso-Craviotto 2009;Banda and Mawadza 2015) that http://repository.uwc.ac.za despite their best efforts, the media may inadvertently perpetuate these stances against migrants through focusing on issues that construct migrants' identity along discourses of crime or delinquency, destitution or cultural conflict. Moreover, SAM's focus on Zimbabwean women migrants is a noble one as a way to make their predicament visible.…”
Section: Discussionmentioning
confidence: 99%